Perceptions of the War Against Terrorism (WAT): a Malaysian case study - Silong, Abu Daud; Hassan, Zaharah; Krauss, Steven Eric (EuroJournals Publishing, Inc, 2008)
Though terrorism has existed for more than 2,000 years, the 9/11 attacks on the U.S. brought international repercussions unlike any previously experienced. In response to the attacks, the U.S. immediately attempted to build a broad-based anti-terrorism coalition in what is known as the “War against Terrorism” (WAT) or “War on Terrorism.” Malaysia has its own experiences with terrorism, such as during the ‘communist emergency’ of the 1950s. In light of Malaysia’s unique history in overcoming terrorism and the present-day WAT, this study aimed to explore Malaysian’s perceptions of the WAT. Findings from the study indicate that Malaysians hold mostly negative views on the WAT, i.e.: they doubt the intentions of the US government; they view the WAT as a fight against Muslims and as a means for US control; they view the military approach as ineffective; they perceive a conscious effort to link terrorism to Islam; they view the Western media as being insensitive to non-Westerners and they believe that the WAT has had little impact on reducing terrorism due to hidden political agendas. Qualitative findings from the study stress the need for counter-terrorism policy makers to identify the root-causes of terrorism in order to develop appropriate socio-economic programs for the poor, marginalized, discontented and discriminated groups in societies.